A high-throughput inhibitor screen for the erythrocyte plasma membrane Ca++ ATPase - Jonathan Chu; Shreyas Annaswamy; Sanjay A. Desai (PLoS ONE, 2026)
The ubiquitous and conserved plasma membrane Ca ++ ATPase (PMCA) actively extrudes Ca ++ from eukaryotic cells and maintains a large Ca ++ transmembrane gradient that permits diverse roles in signaling and cell cycle regulation. Molecular and biochemical studies have linked PMCA to multiple diseases such as sickle cell disease and malaria severity for the PMCA4b isoform on human erythrocytes. Despite its central role in Ca ++ biology, there are no PMCA inhibitors with sufficient specificity to serve as starting points for therapy development. Because such inhibitors of other ion pumps are critical research tools and are important therapeutics for various diseases, we designed and executed a cell-based high-throughput screen for PMCA inhibitors using human erythrocytes. We miniaturized and optimized a Ca ++ efflux assay using extracellular Fluo-8, a soluble Ca ++ sensitive indicator dye. Ca ++ loading, dye concentration and affinity, hematocrit, and assay temperature were all optimized, providing a robust miniaturized assay for PMCA-mediated Ca ++ efflux. A screen of >52,000 diverse compounds was executed with readings at 2 time points to permit detection of inhibitors with varying affinity; addition of excess extracellular Ca ++ helped exclude false positive fluorescence quenchers. A surprisingly low hit rate, ~ 0.01%, suggests that PMCA has relatively few chemical binding sites that interfere with pump activity. As the screen did not yield reproducible hits, a larger screen with more complex chemical libraries is warranted. The optimized assay should enable identification of specific PMCA inhibitors as research tools and potential future therapeutics.